Factors affecting adoption of improved sorghum varieties in Tanzania under information and capital constraints - Aloyce R. Kaliba; Kizito Mazvimavi; Theresia L. Gregory; Frida M. Mgonja; Mary Mgonja (Agricultural and Food Economics, 2018)
Low adoption of agricultural technology is among the main reasons for low farm productivity and high incidence of poverty and food insecurity in sub-Saharan countries including Tanzania. In this study, we examine the factors affecting adoption of improved sorghum varieties using data from 822 randomly selected sample households in northern and central Tanzania. We employ a multiple-hurdle Tobit model to assess the factors affecting adoption after controlling for both capital and information constraints. We also use t-distributed stochastic neighbor embedding to cluster farmers into homogeneous groups. The method allows to reduce the dimensionality while preserving the topology of the dataset, which increases the clustering accuracy. It also superiors for visualization of the clustering results. Results show that radio and other mass media outlets that create awareness will increase adoption among farmers who do not face capital constraint. Some farmers lack basic resources such as land and capital, and subsidies could have a high impact on these farmers. Other farmers simply need assurance on the performance of improved sorghum varieties. Field days, on-farm trials, and demonstration plots could be useful in supporting these farmers. A tailored support system, however, needs a sustained investment in both quantity and quality of services. There is therefore a need to develop a pluralistic research and extension systems that encourage the use of information technologies and community-based organizations to reach specific groups of farmers.
Keywords: O33; Q16; 330; Adoption; Multiple-hurdle Tobit; Sorghum; t-SNE; Two-step cluster analysis; Tanzania